2022
DOI: 10.5851/kosfa.2022.e2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Meat Quality Characteristics and Proteolysis Trends associated with Muscle Fiber Type Distribution between Duck Pectoralis Major and Iliotibialis Muscles

Abstract: Upload this completed form to website with submission ARTICLE INFORMATION Fill in information in each box below Article TitleComparison of meat quality characteristics and proteolysis trends associated with muscle fiber type distribution between duck pectoralis major and iliotibialis muscles Running Title (within 10 words)Proteolysis and meat quality of duck skeletal muscles

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…These results signified that the number and intensity of proteolysis-induced peptides acquired from sarcoplasmic proteins were relatively higher than those acquired from myofibrillar proteins, although both degraded during the storage period. Similar results were observed in our previous study on beef M. longissimus lumborum and M. psoas major and duck PM and IL muscles ( Kim et al, 2021 ; Cheng et al, 2022 ). These studies observed greater degradation of sarcoplasmic proteins than myofibrillar proteins.…”
Section: Discussionsupporting
confidence: 92%
“…These results signified that the number and intensity of proteolysis-induced peptides acquired from sarcoplasmic proteins were relatively higher than those acquired from myofibrillar proteins, although both degraded during the storage period. Similar results were observed in our previous study on beef M. longissimus lumborum and M. psoas major and duck PM and IL muscles ( Kim et al, 2021 ; Cheng et al, 2022 ). These studies observed greater degradation of sarcoplasmic proteins than myofibrillar proteins.…”
Section: Discussionsupporting
confidence: 92%
“…AGPAT gene contributes to the production of diacylglycerol and DGAT gene produces triacylglycerol in the triglyceride metabolic pathway ( Jarc and Petan, 2019 ). Differences in expression levels of these genes between animal breeds identified using RNA-seq technique have been found to be responsible for differences in intramuscular fat content and meat quality ( Cheng et al, 2022 ; Cho et al, 2015 ; Cho et al, 2023 ; Won et al, 2023 ).…”
Section: Transcriptomics Techniques and Application For Meat Qualitymentioning
confidence: 99%
“…Several reports have described significant biochemical and biophysical changes during muscle conversion to meat, and these changes have a direct effect on meat quality [22][23][24][25]. During the postmortem aging process, cytoskeletal myofibrillar protein degradation by endogenous proteases results in significant improvements in the sensory properties of meat [25].…”
Section: Mechanism Of Postmortem Aging On Changes In Meat Qualitymentioning
confidence: 99%